GIANT TEMPEH FESTIVAL: BETWEEN SUBJECT AND GIVEN SUBJECT (A STUDY OF GIANT TEMPEH FESTIVAL IN TLOGOREJO DISTRICT BUMIAJI VILLAGE BATU CITY IN SLAVOJ ZIZEK PERSPECTIVE ABOUT SUBJECT IDENTITY) - Muhammad Hayat (University of Muhammadiyah Malang, 2019)
This research entitled Giant Tempeh Festival: Between subject and given subject was done in Tlogorejo district Bumiaji village, Batu City.